2017
DOI: 10.1080/19490976.2017.1379637
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-associated microbiota dysbiosis in colitis associated cancer

Abstract: Gut microbiota dysbiosis has been associated with inflammatory bowel diseases (IBD). In colorectal cancer, the gut microbiota has also been recognized as potentially involved in aggravating or favoring the tumor development. However, very little is known on the structure and role of the microbiota in colitis associated cancer (CAC), an important complication of IBD in human. Here we analyzed the bacterial and fungal composition of the mucosa associated microbiota of patients suffering CAC, sporadic cancer (SC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 33 publications
10
123
2
2
Order By: Relevance
“…In a study conducted in 2008, F. prausnitzii was reported to protect from inflammation in vitro and in vivo through blocking NF-κB activation and IL8 production [21]. Meanwhile, both F. prausnitzii and its culture supernatant could exhibit anti-inflammatory effects under recovery from chronic colitis and colitis reactivation [22][23][24]. Umesaki and his colleagues found that a defined mixture of 46 strains of Clostridium species belonging to Clostridium clusters XIVa and IV could modify the intraepithelial lymphocytes profile in large intestine [19].…”
Section: Benefits From Crosstalk Between Clostridium Species and Intementioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in 2008, F. prausnitzii was reported to protect from inflammation in vitro and in vivo through blocking NF-κB activation and IL8 production [21]. Meanwhile, both F. prausnitzii and its culture supernatant could exhibit anti-inflammatory effects under recovery from chronic colitis and colitis reactivation [22][23][24]. Umesaki and his colleagues found that a defined mixture of 46 strains of Clostridium species belonging to Clostridium clusters XIVa and IV could modify the intraepithelial lymphocytes profile in large intestine [19].…”
Section: Benefits From Crosstalk Between Clostridium Species and Intementioning
confidence: 99%
“…They can particularly response to F. prausnitzii and exert anti-inflammation effect by promoting the IL10 production dependent on CD39 [23]. 4) Extracellular polymeric matrix (EPM) of F. prausnitzii strain HTF-F induced the TLR2-dependent secretion of IL10 and IL12 in human monocyte-derived dendritic cells (DC cells) to attenuate inflammation [24] the concentration of butyrate. Low-dose butyrate promoted intestinal epithelial proliferation but butyrate at physiologic concentration suppressed proliferation [36].…”
Section: Scfasmentioning
confidence: 99%
“…The activation of MT1/MT2 receptors by melatonin also triggers other signaling pathways, including nuclear factor κ‐light‐chain‐enhancer of activated B cells (NF‐κB), mitogen‐activated protein kinases (MAPK), extracellular‐signal‐regulated kinases 1/2 (ERK1/2), phospholipase C/protein kinase (PLC/PKC), etc. (Figure ) These pathways are involved in multiple regulatory processes from chronobiological regulation to cellular responses to various injuries such as apoptosis …”
Section: Receptors Exert Functions In Melatonin Immunomodulationmentioning
confidence: 99%
“…Další asociace byla nalezena mezi bakteriálním složením střevní mukózy a sporadickými CRC asociovanými s kolitidou, u nichž byl zaznamenán vyšší výskyt bakterií z čeledi Enterobacteriaceae a rodu Sphingomonas a nižší výskyt Fusobacterium a Ruminococcus v porovnání se sporadickými CRC neasociovanými s kolitidou [69].…”
Section: Bakteriální Model "Driver-passenger"unclassified